Elaboración de atlas digital de parásitos intestinales, con muestras de heces recolectadas en la provincia de Loja - González Iñiguez, Evelyn Dayanna (2022)
Parasitology is a branch of science that studies parasitism in general, parasitic diseases rank second in terms of morbidity and mortality, these diseases are related to ecological, immunological, genetic, physiological and nutritional factors, including socio-economic and cultural situations. The objective of this research work was to elaborate a digital atlas of intestinal parasites, with stool samples collected in the Province of Loja; Through a quantitative, descriptive-cross-sectional study, 300 samples were collected, of which parasites were found in 200 samples. The results obtained were presented through a blog, of all the samples collected, 11 intestinal parasites were found, which are: Entamoeba coli, Entamoeba histolytica, Iodamoeba butschlii, Endolimax nana, Giardia lamblia, Blastocystis hominis, Chilomastix mesnili, Ascaris lumbricoides, Enterobius vermicularis, Hymenolepis nana, and Trichuris trihiura. and 2 that were obtained through the purchase of fixed plates: Ancylostoma duodenale and Taenia spp. The techniques used are the direct method, Ritchie method and MIF